Differential Striatal Dopamine Responses Following Oral Alcohol in Individuals at Varying Risk for Dependence. (6th August 2013) - Setiawan, Elaine; Pihl, Robert O.; Dagher, Alain; Schlagintweit, Hera; Casey, Kevin F.; Benkelfat, Chawki; Leyton, Marco
<x xml:space="preserve">Abstract</x> Background The neurobiology of risk for alcohol use disorders (AUDs) remains poorly understood. Individual differences in vulnerability, though, have been indicated by subjective responses to alcohol ingestion and personality traits. Methods To investigate the relationship between these features and striatal dopamine (DA) responses to alcohol, we studied 26 healthy young social drinkers (21.3 ± 3.0 years old; 10.7 ± 8.8 drinks/wk) at varying risk for alcoholism. Each participant received 2 positron emission tomography [11C]raclopride scans after administration of either placebo or oral alcohol (1 ml/kg body weight of 94% alcohol, 0.75 g/kg) in a randomized and counterbalanced design. Results Subjects with high‐risk subjective responses to alcohol had more family members with AUDs, greater alcohol use problems, and, in response to the alcohol challenge, significant decreases in [11C]raclopride binding indicative of increased extracellular DA. In contrast, low‐risk subjects exhibited increases in [11C]raclopride binding in response to alcohol. The results were similar when risk groups were based on personality traits, although statistically less robust. Conclusions Changes in striatal DA in response to alcohol ingestion may be a neurobiological marker of vulnerability to AUDs.